Retroperitoneal cystoadenocarcinoma: a case report with a literature review - Zanoni, Daniele; Sikokis, Angelica; Bersanelli, Melissa; Gnetti, Letizia; Buti, Sebastiano (Acta Biomedica Atenei Parmensis, 2015)
Primary retroperitoneal mucinous cystoadenocarcinoma (PRMC) is an extremely rare clinical entity with about 50 cases described by the literature. Given the rarity of this pathology, the sharing of accurate available informations is important to improve its knowledge. We reported a case of a woman diagnosed with PRMC who received different lines of chemotherapy and radiotherapy and we also performed a review of the literature on the issue. (www.actabiomedica.it)